Microplastic Abundances in the Sediment of Coastal Beaches in Badung, Bali - Maghfira Shafazamilla Mauludy; Agung Yunanto; Defri Yona (Jurnal Perikanan Universitas Gadjah Mada, 2019)
The use of plastic material has increased significantly because of its durability and resistance from degradation. Plastic wastes could degrade into smaller size known as microplastics. The purposes of this study are to analyze and to compare total abundance of microplastic among coastal beaches in Badung, Bali. This study was conducted at five different coastal beaches which are Doublesix Beach, Kuta Beach, Melasti Beach, Mengiat Beach, and Tanjung Benoa Beach. Microplastic abundance was found in the average of 90.7±59.1 particles kg-1. There are three types of microplastic found in this study; film, fiber, and fragment and the abundances were varied among beaches. Fiber dominated all the study areas in the average of 42.8±24.1 particle kg-1. Kuta Beach has the highest amount of microplastic compared to the other beaches with the average of 148.9±103.8 particles kg-1. It might be due to Kuta Beach is the very famous beach visited by many tourists in the Bali Island. Moreover, this study was conducted during monsoon season that has been know to bring plastic wastes to Kuta Beach.